Graphene-metal oxide hybrids for lithium ion batteries and electrochemical capacitors - Wu, Zhong Shuai; Feng, Xinliang; Müllen, Klaus (Walter de Gruyter GmbH, 2014)
The development of novel hybrid materials based on nanocarbons and metal oxides for electrochemical energy storage devices has recently attracted great attention due to the increasing global demand for energy. In this chapter, we review recent efforts dedicated to the fabrication of graphene-metal oxide hybrids as high-performance electrodes for lithium ion batteries and electrochemical capacitors. Several key structural models of graphene-metal oxide hybrids are described, including anchored, encapsulated, sandwich, layered, and mixed models. These structural models benefit from the kinetics of charge transfer, accommodate structural changes during the change/discharge processes, and give rise to enhanced electrochemical properties, such as high capacity, rate capability, cycling stability, and energy/power densities. By studying the structure-property relationships of different hybrids, one can conclude that there are synergetic effects between graphene and metal oxides. This chapter offers new insights into the design and fabrication of novel high-performance graphene-metal oxide electrode materials for energy storage devices.
CRIS-Team Scopus Importer:2023-03-20